Is the Naturalization of the Townscape a Condition of De-Industrialization? An Example of Bytom in Southern Poland - Maksymilian Solarski; Robert Krzysztofik (Land, 2021)
A characteristic element of the transformations of cities in Central and Eastern Europe after 1990 was the emergence of shrinking cities. The main problem related to shrinking cities is around how this process developed as a result of rapidly intensifying de-industrialization. While many studies in this area are devoted to demographic, social, and economic issues, relatively few studies address the spatial dimension. In this article, the example of spatial development in the (post-) mining city of Bytom in southern Poland is discussed, pointing to the need for a multifaceted approach to this issue. This article begins with an attempt to contextualize this issue within a broader time perspective. Such an analysis makes it possible to better situate contemporary changes in the context of the processes that were visible in previous periods. Next, these changes are described using two methods. The basis of the first method is comparisons between the different types of land use. The second method, which is emphasized, is the method of A. Macias, which indicates the degree of naturalization/anthropogenization of space. Macias’ method is crucial in the context of discussions about the future of post-mining towns, where attention is paid, among other things, to the issue of sustainable development.